Iloilo City drivers traffic violators - Gialogo, Ana Bell E.
This study sought to answer the question on what are the usual traffic violations committed by public/private vehicle drivers plying Iloilo City. Specifically, what are the factors that led the drivers to commit violations? Who are the violators among these drivers? How often these violations occur? And how can such violations be solved? More importantly, this study considers the following hypotheses : (1) there is an increase in the number of traffic violators arrested by traffic enforcers during rush hours; (2) there are factors that contribute to the violation of rules and regulations of PUV drivers; and (3) private and public utility vehicle drivers usually commit common violations. The study made use of a descriptive research design. Respondents were the public/private drivers in Iloilo City who were identified through random and incidental samplings. Data were collected by distributing questionnaire and by personal interview. These instruments were administered and data obtained were processed for analysis.Frequency counts and percentages were used for the interpretation of data. As a conclusion, there are factors that contribute to the commission of the traffic violations by drivers. To solve the problem on traffic violations by drivers, the group has recommended that drivers should be given seminars, training and workshop on traffic twice aa year and traffic rules and regulations should be imposed strictly and consistently.